GAMBARAN TINGKAT PENGETAHUAN BIDAN DAN PERAWAT TENTANG PEMBERIAN VITAMIN K PADA BAYI BARU LAHIR DI PUSKESMAS KECAMATAN MESUJI TIMUR TAHUN 2022 - Aprellia Irianti Irianti; Muhammad Yunus; Arti Febriyani Hutasuhut; Astri Pinilih (CV. Jasa Sukses Abadi, 2022)
Background: Vitamin K is a fat-soluble vitamin that has an important role in activating substances that play a role in blood clotting. Neonates tend to have relatively lower levels of vitamin K and vitamin K reserves in the liver compared to neonates. This causes newborns to tend to have vitamin K deficiency. Objective: To describe the level of knowledge of midwives and nurses about giving vitamin K to newborns at the Puskesmas Mesuji Timur District in 2022. The type of research used is descriptive with a cross sectional design. The sample in this study were midwives and nurses at the Mesuji Timur District Health Center with a total of 65 people. Results: In this study, the frequency of sufficient knowledge level of respondents was 47 people with a percentage of 72.3%. The conclusion of this study is that midwives at the Puskesmas Mesuji Timur District have good knowledge of 16%, 38% enough and less 8%. Nurses at the Puskesmas Mesuji Timur District have good knowledge of 26,7%, enough 60% and less 13,3%.